Charitable food aid in the Slovenian welfare state - Budimir, Miroslav (Socialno delo, 2025)
Charitable food aid has been one of the most important responses to food poverty/insecurity in wealthy First World countries since the early 1990s. Exacerbation of the dual social-ecological crisis in the following decades served as the main justification for the institutionalization of the ecosocial policy programme of charitable surplus food redistribution (CSFR) in the EU member states. The focus of this paper is the impact of charitable food aid/surplus food redistribution on the welfare state in Slovenia. The paper is based on the primary empirical data collected from the major CSFR institutions and organizations in seven social work regions in Slovenia. The author finds that institutionalization and entrenchment of charitable food aid pushes the Slovenian welfare state further in the direction of a residual (neo)liberal welfare regime. In general, this ecosocial policy programme, strongly supported by the major EU funding instruments, proves that universalistic social model based on the principles of social solidarity and human rights has been abandoned in favour of charity-based short-term band-aid solutions that don’t tackle the root structural causes of poverty.
Keywords: charity; dobrodelnost; ecosocial policy; ekosocialna politika; food insecurity; poverty; prehranska negotovost; presežki hrane; revščina; social-ecological crisis; socialno-ekološka kriza; surplus food